The relationship of fetal heart rate at 10-14 weeks and birthweight at term - Panyu Panburana (2018)
The purpose of this study was to examine the correlation between the fetal heart rate at 10-14 weeks and birthweight at term. At the fetal medicine unit, Ramathibodi Hospital, the screening for Down's syndrome at 10-14 weeks' gestation by ultrasound has been ongoing since January 1997. Transabdominal ultrasound examination is routinely performed for the crown-rump length, nuchal translucency thickness and fetal heart rate. The fetal heart rate is measured over four to six cardiac cycles by using the pulsed Doppler technique. One thousand and fourteen term singleton pregnancies that resulted in phenotypically normal live births were studied. The study was done was carried out at 10-14 weeks of gestation (mean 12.27 weeks) from January 1997 to November 1997. The mean patient age was 26.78 years old. The mean gestational age and birthweight were 38.83 weeks and 3,097.83 grams respectively. The incidence of low birthweight (less than 2,500 grams) was 14.2 per cent. Regression analysis demonstrated no significant relation between fetal heart rate at 10-14 weeks and birthweight at term. In conclusion, the result of this study revealed that there was no correlation of the fetal heart rate at 10-14 weeks' gestation and birthweight at term.